Síndrome de alienação parental : um estudo através do olhar de psicólogos e assistentes sociais peritos - Melo, Ana Katarina Leimig Saraiva de (2013)
Parental Alienation is a phenomenon that borns within the family when they have any custody conflict, mainly in the judicial sphere, that in a short period became focus of cientific studies in Psychology, Psychiatry and Law. In this context, some searches and discutions about this subject are needed, to contribute to a further deepening in practice of Clinic Psychology as Judicial scope, aiming ways of prevention and promotion of total welfare of childs and teenagers victims of Parental Alienation. This research is qualitative aimed to understand the consequences of Parental Alienation Syndrome (PAS) in the family, through the eyes of Professional Psychology and Social Work dealing with the subject. The instrument for data collection was a semi-structured interview. Participants were three Psychologists and three Social Service experts, linked to the Judiciary of Pernambuco. The data was analyzed using Minayo s thematic, enabling to understand the meaning of speech of interviewees according to the proposed objectives. The main results point to a program developed gradually, by professionals, for the purpose of issuing an opinion that seeks to clarify the family context in which children are inserted, and not worry about the way it operates of experts in order protect the child and / or adolescent from the consequences of a bad breakup elaborate.